2016
DOI: 10.1515/nanoph-2016-0102
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast ammonia-driven, microwave-assisted synthesis of nitrogen-doped graphene quantum dots and their optical properties

Abstract: Abstract:For the first time, a facile, ultrafast, ammoniadriven microwave-assisted synthesis of high-quality nitrogen-doped graphene quantum dots (NGQDs) at room temperature and atmospheric pressure is presented. This one-step method is very cheap, environment friendly, and suitable for large-scale production. The as-synthesized NGQDs consisting of one to three graphene monolayers exhibit highly crystalline quality with an average size of 5.3 nm. A new fluorescence (FL) emission peak at 390 nm is observed, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 38 publications
4
73
0
Order By: Relevance
“…Absorption peaks at approximately 205 nm (6.05 eV), 230 nm (5.39 eV), 330 nm (3.76 eV), and 400 nm (3.10 eV) are present in the spectrum of the N‐GQDs. Absorption at 205 and 230 nm indicated π → π * C=C transitions, and absorption at 330 and 400 nm indicated n → π * C = O and C–N transitions, respectively . The fluorescence emission spectra of the GQDs and N‐GQDs at different excitation wavelengths are shown in Figure b,c, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Absorption peaks at approximately 205 nm (6.05 eV), 230 nm (5.39 eV), 330 nm (3.76 eV), and 400 nm (3.10 eV) are present in the spectrum of the N‐GQDs. Absorption at 205 and 230 nm indicated π → π * C=C transitions, and absorption at 330 and 400 nm indicated n → π * C = O and C–N transitions, respectively . The fluorescence emission spectra of the GQDs and N‐GQDs at different excitation wavelengths are shown in Figure b,c, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…N‐GQDs have been synthesized using glucose, glycine, or citric acid as a carbon source and ammonia, glycine, tris(hydroxymethyl) aminomethane, or 3,4‐dihydroxy‐ l ‐phenylalanine as a nitrogen source. Zheng et al reported an ultrafast, ammonia‐driven, microwave‐assisted N‐GQD synthesis with glucose and ammonia, which were placed in a commercial microwave oven at 900 W for 1 min. This one‐step, microwave‐assisted synthesis of high‐quality N‐GQDs was performed at room temperature (25 ± 1°C) and atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GQDs possess stacked graphene-like sp 2 carbon-type layer structures inside the dots, endowing them with some of the unusual properties of graphene such as unique edge effects and quantum confinement, leading to broadband optical absorption [24,25]. GQDs have attracted increasing interest in many fields, such as electrochemical biosensors, photoelectrochemical biosensors, drug delivery, bioimaging, and energy conversion [26][27][28][29]. Furthermore, both theoretical and experimental results have indicated that the introduction of nitrogen atoms into the carbon lattice of quantum dots (NGQDs) would tailor the electronic property and chemical reactivity of GQDs [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…One efficient strategy to overcome the drawbacks and improve the electrochemical performance of the electrode is through structure design, such as nanoparticles, nanotubes, and porous balls . These structures not only easily enlarge the contact area between electrode and electrolyte, but also reduce the path length for lithium ions .…”
Section: Introductionmentioning
confidence: 99%